Hubungan Kualitas Pelayanan dengan Kepuasan Pasien Rawat Inap BPJS Kelas III (Studi Kasus di RSU Haji Surabaya) - Fitria, Aidil; Radjikan, Radjikan; Susiantoro, Adi (JPAP: Jurnal Penelitian Administrasi Publik, 2019)
AbstractHealth service is a basic right owned by the government, along with improving the living standards of human being better and see the performance of government bureaucracy that is still far from public expectation, the government in this case the general is required to improve itself to improve health service for the community, at impatient BPJS class III. Since BPJS and other government programs, currently based on assessment, the quality of health services, especially in patient care, is more likely to decline if assessed in terms of patient satisfaction. This study aims to analyze the quality of service with the satisfaction of patients through the seven dimensions the quality of service consisting of assurance, empathy, reliability, responsiveness, tangible, core medical service and professionalism. The dimensions used to analyze the quality of service with the hospitalizations satisfaction patients BPJS class III in the RSU Haji Surabaya. Methods used in this research using the description of qualitative, sources used data is the primary data and secondary related to the situation and conditions. In this study author also use a technique research in the form of observation, interview and documentation in order to obtain the data primary to know how the quality of service with the patients BPJS class III satisfaction of the hospitalizations in the RSU Haji Surabaya. Based on the results of data analysis and discussion that has been done, the quality of service with the hospitalizations satisfaction patients BPJS class III in the RSU Haji Surabaya, according to the dimension of assurance, empathy, reliability, responsiveness, core medical service and professionalism the quality of service the hospitalizations third grade in RSU Haji Surabaya can be said good so that the patient was satisfied.Â Keywords: Quality of service, Patient satisfaction, the quality of service with the patient relationship satisfaction